ANALISA BEST PRACTICE SERVICE LEVEL MANAGEMENT (SLM) CISCO MENGGUNAKAN KRITERIA KELENGKAPAN DARI THOMAS SCHAAF - Indra Waspada (Department of Informatics, Universitas Diponegoro, 2010)
Service Level Agreement (SLA) is an important document to facilitate IT service provisioning by clearly defined Quality of Service (QoS) parameters. The management of SLA is the main subject in the discipline of Service Level Management (SLM). SLM is very important to improve relationship between IT service provider and its customer. It delivers documented agreement as a common understanding of expectation and possible achievements to the agreed cost. It means SLM builds the interface between an IT organization and its customer, so it plays a critical and important role in the context of IT service management. In this paper, an SLM best practice from CISCO will be analyzed with the assessment criteria of SLM framework by Thomas Schaaf. The result will be followed with several suggestion to fulfil the gap in this CISCO’s best practice.